Characterization of 56 airborne persistent organic pollutants (POPs) in gas-phase and particle-phase. Issue 1 (4th March 2022) - Tan, Li; Wang, Ning; Dong, Yingjian; Li, Siyuan; Wang, Xuehan; Zhang, Guiqin
Abstract: A systematic investigation was conducted on 56 persistent organic pollutants (POPs) in the atmosphere at seven functional regions of Jinan, China. The POPs included 16 polycyclic aromatic hydrocarbons (PAHs), 6 phthalic acid esters (PAEs), 17 polychlorinated biphenyls (PCBs), and 17 organochlorine pesticides (OCPs). The concentrations in gas-phase and particle-phase were monitored and analyzed to assess the contamination status and to identify the pollution sources according to the mass ratios between POP congeners and the distribution among the sampling regions and periods. The results show that the pollution level at a recreational area was lower than that in other regions of the city and it was higher in winter than in summer for all the 7 sampling sites. Sixteen polycyclic aromatic hydrocarbons (PAHs) were evenly distributed between gas-phase and particle-phase. The total concentration of phthalic acid esters (∑PAEs) in particle-phase was 96.4% larger than that in gas-phase, which was possibly derived from artificial plastics. PCB-126 was one of the major pollutants of the 17 polychlorinated biphenyls (PCBs) in the atmosphere. High-Cl PCBs favored adhering to airborne particles, while low-Cl PCBs tended to stay in gas-phase. The total concentration of 17 organochlorine pesticides (∑OCPs) in gas-phase accounted for 68.0%, while methoxychlor, dieldrin, and endrin aldehyde preferred to particle-phase. Additionally, the preliminary investigation suggests that local pollution sources contributed to most PAHs in urban sites, while the sources could be complex for the suburban area and adjacent towns in winter. Residues of some OCPs could also come from long-distance transportation.